IMPLEMENTASI PROGRAM PENANGANAN ANAK JALANAN DI KOTA SEMARANG - Fadoli, M. Irsyad; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2017)
The impact of poverty in Indonesia is that there are many street children who are spread almost throughout the territory of Indonesia. The problem of street children is as if no settlement is marked by the increasing number of street children in Indonesia. Semarang city is one of the cities with a high distribution of street children. Semarang city government has issued a Local Regulation to address the street children in the city of Semarang. The purpose of the regulation is dealing with street children so they can return to normal life as children in general. In this study, researchers discuss how the implementation of policies to deal with street children in the city of Semarang and to investigate the obstacles in the process of implementation is. Based on the results of research conducted, the implementation of policies to deal with street children in the city of Semarang is not running optimally. Less than optimal implementation of this program can be seen from the results of program performance that has not been achieved as well as of the obstacles encountered, ie internal constraints implementing policies such as the problem of coordination between the implementing agencies, the resources both human resources and financial resources are not sufficient and also constraints of the target of the program itself, namely the social and economic conditions were less positive attitudes of the target group program goals. The results of this study can be concluded that the implementation of program of the handling of street children in the city of Semarang already implemented but not yet optimal. Constraints faced cause. Advice from researchers is more increased relationships between organizations implementing policies and also to approach closer to the street children by working with foundations of street children in the city of Semarang.